The Impact of Chinese College Students' Perceived Stress on Anxiety During the COVID-19 Epidemic: The Mediating Role of Irrational Beliefs - Chi, Zhang; Qian, Liu; Haihua, Liu; Nuoxun, Lin (Frontiers in Psychiatry, 2021)
Objective: To explore the underlying mechanism of the impact of perceived stress on anxiety of the Chinese college students during the COVID-19 epidemic. Methods: The Perceived Stress Scale, Irrational Belief Scale, and General Anxiety Scale were adopted in the current study. College students were randomly selected for online questionnaire survey. There were 1598 valid questionnaires, and the proportion of women was 47.81%. Results: The perceived stress and anxiety, as well as the three dimensions of irrational beliefs (catastrophizing, low frustration tolerance, and depreciation) were significantly positively correlated; further analysis found that the perceived stress had a significant positive predictive effect on the anxiety of college students. Catastrophizing, low frustration tolerance, and depreciation played part of the mediating role, and there was no significant difference in the strength of these mediating roles. Conclusion: The perceived stress of the COVID-19 epidemic had a positive effect on the anxiety of Chinese college students, this was partly mediated by irrational beliefs.